EFFECT OF GAMMA IRRADIATION ON THE GROWTH AND DEVELOPMENT OF SAGO PALM (Metroxylon sagu Rottb.) CALLI - Imron Riyadi; Sumaryono Sumaryono (Indonesian Journal of Agricultural Science, 2016)
The application of gamma irradiation on plant materials may increase the genetic variation of the offspring with useful traits. The experiment was conducted to determine the effect of irradiation dosage of gamma ray on growth and development of sago palm (Metroxylon sagu) calli. Friable calli of sago palm derived from suspension culture were used as a material source. The primary calli were initiated from apical meristematic tissues of sago palm suckers of Alitir variety from Merauke, Papua. The treatments used were dosage of gamma ray irradiation at 0, 5, 10, 15, 20 and 25 Gy. The treated calli were then subcultured on modified Murashige and Skoog (MMS) solid medium containing 3% sucrose and 0.1% activated charcoal and added with 1 mg l-1 2,4-D and 0.1 mg l-1 kinetin. The results showed that at all irradiation dosages, calli biomass increased significantly. The highest proliferation of calli biomass of 5.33 folds from the initial culture after 4 weeks was achieved at gamma irradiation of 25 Gy, whereas the lowest proliferation of calli biomass of 3.4 folds was achieved at control. The best development of embryogenic calli was obtained at 10 Gy that produced 100% somatic embryos, whereas the lowest somatic embryo formation at 0% was obtained at 0 and 25 Gy after one subculture. High response of somatic embryo induction to gamma irradiation at 10 Gy may increase production of somatic embryos. These results can be used in in vitro breeding of sago palm via mutagenesis to create new elite varieties.